Analisis Strategi Bersaing dalam Upaya Meningkatkan Jumlah Nasabah Produk Pembiayaan Warung Mikro - Mahfud, Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2020)
Warung Microfinance is Bank financing to individual customers or business entities engaged in the MSME sector to finance their business needs through working capital financing or investment financing. This product is not only owned by banks, but other Islamic banks also own it. To face competition between banks, each bank must have a different competitive strategy. This description is a type of qualitative research that aims to find out the procedures for financing micro stalls, the competitive strategies used and the obstacles encountered in implementing the competitive strategy. Data analysis using descriptive methods. To obtain valid data, the author uses several data collection techniques, namely observation, interviews and documentation. The results of this study state that the procedure for financing a micro shop at the Bank is very easy. Customers come to the bank office with the requirements for financing a micro shop and then the paperwork will be taken care of by the administration. If it is complete and meets the requirements, it will be continued by signing the agreed contract. The competitive strategy used by the Bank is to provide a low mark up rate, more varied products and a low repayment rate. Constraints faced in the implementation of this competitive strategy are disbursement that is not timely (disbursement of funds stretched), other banks offer lower prices / mark-ups and lack of employees.